An integrated dual strategy to control Fusarium graminearum sensu stricto by the biocontrol agent Streptomyces sp. RC 87B under field conditions. Reprint - Palazzini, Juan Manuel; Yerkovich, Nadia; Alberione, Enrique Javier; Chiotta, María Laura; Chulze, Sofia Noemí (2018)
Fusarium head blight (FHB) caused by species within the Fusarium graminearum complex is a devastating disease that causes extensive yield and quality losses to wheat in humid and semi-humid regions of the world. The disease can cause not only yield losses but also grain contamination with mycotoxins such as deoxynivalenol (DON). Several epidemics have occurred in Argentina, the last in 2012, with yield losses up to 70%. Control of the disease is partially achieved by chemical treatments, crop rotation, breeding for resistance and tillage practices. Biocontrol can be used as part of an integrated pest management. The objetives of this study were: 1- to evaluate the biological control effect of Streptomyces sp. RC 87B on FHB disease incidence, severity and DON accumulation and 2- to evaluate if Streptomyces sp. RC 87B reduces F. graminearum inoculum when applied to wheat stubble. Streptomyces sp. RC 87B was applied at wheat anthesis to determine effects on FHB disease parameters and over wheat stubble left after harvest to evaluate effects on the survival of F. graminearum. FHB incidence and severity were visually estimated and DON content was assessed by HPLC after harvest. On stubble, F. graminearum prevalence was monitored by using TaqMan PCR for 180 days. A significant disease severity and DON reduction were observed with the biocontrol treatments during the field trials (29–39% and 69–85%, respectively), but no reduction on disease incidence was achieved. On wheat stubble, Streptomyces sp. 87B reduced F. graminearum inoculum after 45 days (82%) and after 90 days no inoculum was detected in the first of two trials. In a second trial, a significant reduction (46%) in F. graminearum inoculum was observed after 90 days. The biocontrol strain Streptomyces sp. 87B showed high potential for contributing to the reduction of FHB on wheat at different times in the F. graminearum life cycle.